Analisis Fasilitas Kearsipan di BPJS Ketenagakerjaan Rawamangun - Fitriyani Nurul Awalliah; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to determine the condition and completeness of archival facilities at BPJS ketenagakerjaan rawamangun, to determine the standard of archival facilities at BPJS ketenagakerjaan rawamangun, and to find out solutions in maintaining archival facilities at BPJS ketenagakerjaan rawamangun. This research uses a qualitative method with a descriptive approach, which focuses on direct observation of phenomena or situations in their original conditions. The data collected consists of primary and secondary data. Data collection techniques include interviews, observation, and documentation, which are conducted directly from the source. Based on the results of the research, the archival facilities available at BPJS Ketenagakerjaan Rawamangun are considered quite adequate. However, there are several obstacles found, such as the lack of completeness of facilities and less than optimal maintenance of existing facilities. As a solution, it is recommended that the completeness of archival facilities be improved immediately. In addition, there needs to be more attention to the care and maintenance of archival facilities to maintain their quality and sustainability.